Guidelines for the provision of echocardiography in Canada: recommendations of a joint Canadian Cardiovascular Society/Canadian Society of Echocardiography Consensus Panel - Sanfilippo, Anthony J; Bewick, David; Chan, K L; Cujec, Bibiana; Dumesnil, J G; Honos, George; Munt, Brad; Sasson, Zion; Tam, James; Tomlinson, Charles; Aboguddah, Ayman; Ahmed, Shaheeda; et al. (Canadian journal of cardiology, 2005)
Recognizing the central role of echocardiographic examinations in the assessment of most cardiac disorders and the need to ensure the provision of these services in a highly reliable, timely, economical and safe manner, the Canadian Cardiovascular Society and Canadian Society of Echocardiography undertook a comprehensive review of all aspects influencing the provision of echocardiographic services in Canada. Five regional panels were established to develop preliminary recommendations in the five component areas, which included the echocardiographic examination, the echocardiographic laboratory and report, the physician, the sonographer and indications for examinations. Membership in the panels was structured to recognize the regional professional diversity of individuals involved in the provision of echocardiography. In addition, a focus group of cardiac sonograhers was recruited to review aspects of the document impacting on sonographer responsibilities and qualification. The document is intended to be used as a comprehensive and practical reference for all of those involved in the provision of echocardiography in Canada.